2018
DOI: 10.21276/apalm.2049
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Histopathological Patterns and Mast Cells in Cutaneous Lichen Planus and Lichenoid Lesions

Abstract: Background: Besides lichen planus various other skin lesions like erythema multiforme, pityriasis lichenoides, etc., show lichenoid reaction pattern. This study was aimed to compare the histological features and number of mast cells in cutaneous lichen planus and lichenoid lesions. Studies have shown increase in mast cell numbers in mucosal lichen planus and lichenoid lesions. Methods: Tissue sections of lichen planus and lichenoid lesions, (forty samples for each group) were studied. All the epidermal, dermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Our study was conducted to find the histomorphological spectrum of lichenoid dermatitides in our hospital cases and their concordance with the clinical diagnosis. In our study, there was a female preponderance, 28 were female (62.2%) out of the 45 cases which were in concordance with a study by Priya et al, 5 which also showed a female preponderance of 62.5%. Likewise in a study by Kumar et al,6 38 (42.2%) were male and 52 (57.7%) were female and in the study by Parihar et al, 7 the male-to-female ratio was 0.8:1 which was the same as in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Our study was conducted to find the histomorphological spectrum of lichenoid dermatitides in our hospital cases and their concordance with the clinical diagnosis. In our study, there was a female preponderance, 28 were female (62.2%) out of the 45 cases which were in concordance with a study by Priya et al, 5 which also showed a female preponderance of 62.5%. Likewise in a study by Kumar et al,6 38 (42.2%) were male and 52 (57.7%) were female and in the study by Parihar et al, 7 the male-to-female ratio was 0.8:1 which was the same as in our study.…”
Section: Discussionsupporting
confidence: 93%